Konsep Video Konten Edukasi Kesehatan Mental untuk Remaja - Imandina, Kharisa; Sutejo, Aris; Yani, Aditya Rahman (Jayapangus Press, 2024)
Mental health is one of the most highlighted health issues by many people around the world. During this time, many adolescents experience mental health problems. The most common mental health problem in adolescents is depression or anxiety. Deviant behavior to harm oneself, as a result of a lack of understanding in the management of adolescent emotions, is one of the reasons why the phenomenon of suicide itself comes from the individual concerned who is experiencing social problems. The purpose of making this video concept is to educate adolescents in understanding emotional management, how to develop themselves in the environment, and provide information and raise awareness of adolescents about the importance of maintaining mental health. In designing this video concept, primary and secondary data were collected from interviews and observations. In analyzing the data, using fishbone analysis and 5W + 1H. In designing the concept of this content video, it pays attention to aspects of its function to educate teenagers that are not boring and easy to understand. For an emotional attachment by providing a color mood according to the background of the situation. There is an explanation of emotional management and self-development in the environment in teenagers which aims to educate teenagers about the importance of mental health for themselves and others. Self-development is needed to explore and increase the potential that exists within teenagers. It is hopefully that the design of mental health educational content videos can provide new insights for adolescents and the messages conveyed can be well received.